Analytical solutions for the self‐ and mutual inductances of arbitrary triangular coils with rectangular cross‐section. Issue 6 (13th February 2018) - Wu, Dehui; He, Tianfu; Wang, Xiaohong; Sun, Qisheng
Abstract : A new analytical solution for the self‐ and mutual inductances of arbitrary triangular coils with rectangular cross‐section is presented. Firstly, the electromagnetic field problem of a filamentary triangular coil is solved based on second‐order vector potential. Then, the solution is effectively extended to the arbitrary triangular coil with different track widths by changing the radius of its inscribed circle. A series of new formulae are given for calculating electromagnetic field, self‐ and mutual inductances of triangular coils with different shapes, separation distances, lateral misalignments or angular misalignments. Finally, the verification experiments are carried out on a series of irregular and regular triangular coils. Also, the experimental results show that the measured values are in good accordance with the calculated ones.